An integrated mathematical model for production scheduling and preventive maintenance planning. Issue 6 (24th April 2020) - Kolus, Ahmet; El-Khalifa, Ahmed; Al-Turki, Umar M.; Duffuaa, Salih Osman
Abstract : Purpose: The integration between production scheduling and maintenance planning is attracting the attention of planners in the manufacturing sector with the increase in global competitiveness. Researchers have developed various methodologies to optimize integrated decisions in planning and scheduling, including mathematical modeling under different conditions. This paper considers the simultaneous scheduling of production and maintenance activities with the objective of minimizing the expected total tardiness cost on a single machine (production line). Design/methodology/approach: Scheduling in these two types of activities, production and maintenance, are traditionally done independently, causing conflicts between the two functional areas. To eliminate or at least reduce conflicts, the scheduling of both activities can be done simultaneously with the objective of meeting due dates and maintaining maximum machine availability. In this paper, a mathematical model for an integrated problem is developed and demonstrated by an example. Findings: The proposed integrated model shows a high potential for significant improvements in performance with respect to the cost of tardiness in delivery and machine availability. This is demonstrated by an example showing an average savings of approximately 40%. Originality/value: This substantial saving is owed to the integration of two important decision-making processes in manufacturing systems. Although the integrated problem is complex and difficult to solve, the fact that it is savings driven makes the problem of interest to researchers and practitioners in manufacturing.